System and method for dual fluidized bed gasification - APANEL GEORGE; WRIGHT HAROLD A (2013)
A system, for production of high-quality syngas, comprising a first dual fluidized bed loop having a fluid bed conditioner operable to produce high quality syngas comprising a first percentage of components other than CO and H2 from a gas feed, wherein the conditioner comprises an outlet for a first catalytic heat transfer stream comprising a catalytic heat transfer material and having a first temperature, and an inlet for a second catalytic heat transfer stream comprising catalytic heat transfer material and having a second temperature greater than the first temperature; a fluid bed combustor operable to combust fuel and oxidant, wherein the fluid bed combustor comprises an inlet connected with the outlet for a first catalytic heat transfer stream of the conditioner, and an outlet connected with the inlet for a second catalytic heat transfer stream of the conditioner; and a catalytic heat transfer material.